Space and security a reference handbook - Hays, Peter L. (Contemporary world series, 2011)
During the Cold War era, space was an important arena for the clashing superpowers, yet the United States government chose not to station weapons there. Today, new space security dynamics are evolving that reflect the growing global focus upon the broad potential contributions of space capabilities to global prosperity and security. Space and Security: A Reference Handbook examines how the United States has developed and implemented policies designed to use space capabilities to enhance national security, providing a clear and complete evaluation of the origins and motivations for U.S. national security space policies and activities. The author explains the Eisenhower Administration's quest to develop high-technology intelligence collection platforms to open up the closed Soviet state, and why it focused on developing a legal regime to legitimize satellite overflight for the purposes of gathering intelligence.